LEARNING ENGLISH ACROSS CULTURES-A REFLECTION ON CHALLENGES FACED BY ONLINE LEARNERS AND THEIR MITIGATION STRATEGIES - Badrul Hisham Ahmad; Norkhairi Ahmad (FRASA: ENGLISH EDUCATION AND LITERATURE JOURNAL, 2022)
This study sets out to investigate learners’ cross-cultural experience of learning English for Specific Academic Purposes (ESAP) course from an international instructor via online setting. The objectives of this study were to investigate a) the learners’ feedback on the overall online learning experience, b) the challenges that the learners have experience during their online lessons and c) learners’ strategies in overcoming the challenges experienced during their online lessons. Qualitative data is elicited via purposive sampling from five diploma students enrolled in the ESAP course at a public university in Malaysia. Focus group and follow up individual interviews were utilised to gather feedback on their general cross-cultural learning experiences online learning experience as well as the challenges they encountered during their lessons and their strategies in overcoming those challenges faced during their lessons. The study found that learners perceived their online language learning experience in cross-cultural setting as a positive one. They shared several challenges experienced during the lessons and some strategies that they utilized to manage the challenges.